2016
DOI: 10.1177/1359105316676332
|View full text |Cite
|
Sign up to set email alerts
|

Promoting post-traumatic growth in cancer patients: A study protocol for a randomized controlled trial of guided written disclosure

Abstract: This multicenter study investigates the efficacy of the guided disclosure protocol in promoting post-traumatic growth, through meaning reconstruction, in cancer patients after adjuvant chemotherapy. Participants will be randomized to guided disclosure protocol or to an active control condition. Both conditions consist of three 20-minute writing sessions. Experimental participants verbalize emotions, describe events, and reflect on trauma effects. Control participants write about their past week's daily routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…A useful intervention, in line with this notion, was described by Cafaro and colleagues . They found that using guided disclosure protocol through meaning reconstruction in cancer patients following adjuvant chemotherapy promoted their PTG.…”
Section: Discussionmentioning
confidence: 85%
“…A useful intervention, in line with this notion, was described by Cafaro and colleagues . They found that using guided disclosure protocol through meaning reconstruction in cancer patients following adjuvant chemotherapy promoted their PTG.…”
Section: Discussionmentioning
confidence: 85%
“…For decades, clinicians and researchers have described “meaning making” after stressful experience as one mechanism of processing and coping with traumatic experience (Park, 2010; Rajandram et al, 2011). Supporting those who are searching for meaning after stressful experience and facilitating new understandings that relieve distress is a core component of meaning-centered therapy, cognitive therapies, and other psychotherapeutic interventions (Cafaro et al, 2016; Hayes et al, 2007; Van der Spek et al, 2017). In this article, we summarize meaning-making concepts and literature, present the results of a qualitative analysis of meaning making in cancer survivors, and discuss these results in the context of the literature and practitioner implications.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions aimed to enhance inner resources of these individuals and help them to find a meaning in their experience of skin disease might reduce psychological distress and improve spiritual well-being by restoring a more adaptive sense of self and the world. Indeed, there is evidence showing that individuals can receive substantial help in finding new meaning and purpose in life through expressive writing interventions, which may favor psychological growth in chronic disease ( Cafaro et al, 2019 ) and play a role in enhancing treatment efficacy and quality of life ( Paradisi et al, 2010 ). This study also suggests that clinical or health psychologists working with individuals with chronic skin diseases should have training in the spiritual dimensions of illness.…”
Section: Discussionmentioning
confidence: 99%